Identification of Genomic Markers By RAPD-PCR Primers in Iraq Breast Cancer Patients - Ismaeel, Haneen (Iraqi Journal of Science, 2023)
Random Amplification of Polymorphic DNA (RAPD) analysis was used in this study to direct the attention toward increasing the efficiency of early diagnosis of breast cancer in clinical laboratories at Iraq using recent PCR-dependent protocols and investigate DNA polymorphisms in addition to the detection of genomic markers. Blood samples were collected from 12 diagnosed females with breast cancer (malignant) patients, 12 females with breast benign tumor and 12 controls (normal females). DNA was extracted and RAPD-PCR was performed. The results showed unique profiles of amplified DNA fragments produced in genomic DNA of breast tumors by an arbitrary primers of A8, A11, A12, A13, A15 and A18. Out of the 6 primers used, 1 primer produced monomorphic bands namely primer A13. While other 5 primers produced polymorphic bands. Efficiency and discriminatory power of the polymorphic primers ranged from 0.173-0.057 and 9.5-28.5% respectively. Primer A18 produced the highest number of bands (21 bands) and primer A15 produced the largest molecular band (3.204 Kb) while primer A8 and A15 produced the lowest number of bands (11 bands), primer A11 produced the smallest molecular weight band of (0.166 Kb). Primer A11 produced a band of (0.559 Kb) which showed significant frequency of 100% with Breast benign tumor patients and 83.33% with Breast malignant tumor patients in comparison to control individuals which is completely absent. So, the detected DNA polymorphisms by the arbitrary primers might find application in developing efficient RAPD primer for breast cancer early diagnosis in clinical laboratories at Iraq.